1967-1974 Döneminde Kıbrıs Sorunu ve Türkiye ile Yunanistan’ın Kıbrıs Politikaları / The Cyprus Question in the Period 1967-1974: Turkish and Greek Policies on Cyprus - Kıralp, Şevki (Journal of History Culture and Art Research, 2018)
Abstract The main goal of this paper is to analyze political attitudes of Turkish Cypriot and Greek Cypriot, as well as Turkish and Greek politics towards the Cyprus Question from 1967 to 1974. The relevant period played a crucial role in shaping the political process leading to the Greek coup and Turkish intervention of 1974. Therefore, it might be presumed that analyzing the political developments within this period is likely to provide a contribution for the literature. The historical research covered by this paper starts with 1967 since it was the year that the Junta of Colonels seized power in Greece. Additionally, in late 1967, a Turkish Cypriot village was attacked by Greek Cypriot forces led by General Grivas. As a consequence Turkey asked for, and obtained the removal of the Greek forces that were, in a way contradictory to Zurich-London treaties, stationed on the island in 1964. The historical research ceases with 1974 incidents since the Greek coup and the Turkish intervention overwhelmingly re-shaped the political destiny of Cyprus. This study examined historical sources written in Turkish, Greek and English (archival materials, newspapers and memoires) to shed light on the relevant political developments. The research conducted by this paper reached to the conclusion that the Greek Cypriot leaders tried to limit Turkish Cypriots’ veto rights by amending the constitution, and the Turkish Cypriot leaders tried to provide local autonomy for their community. Moreover, while there were significant conflicts and tensions between Greece and Greek Cypriot leaders, the relations between Turkey and Turkish Cypriot leaders were based on harmony and cooperation. Öz Bu çalışmanın temel amacı, 1967-1974 yılları arasında adadaki Türk ve Rum toplumları ile Türkiye ve Yunanistan’ın Kıbrıs Sorununa nasıl yaklaştıklarını incelemektir. Bu dönemin Kıbrıs, Türkiye ve Yunanistan’ın siyasi tarihleri açısından önem taşıyan 1974 gelişmelerini şekillendiren bir süreç olmasından ötürü, ilgili tarafların bu yıllardaki siyasetlerini incelemenin literatüre katkı sağlayacağı düşünülmektedir. 1967, Yunanistan’da Albaylar Cuntasının iktidara geldiği, bir yandan diplomatik çabalar sürerken diğer yandan General Grivas komutasındaki Rum askeri birliklerinin bir Türk köyüne saldırdığı, bunun sonrasındaysa Türkiye’nin tutumunu sertleştirerek adaya 1964 yılında Zürih-Londra antlaşmalarına aykırı biçimde yerleştirilen Yunan birliklerinin Kıbrıs’tan çıkarılmasını sağladığı bir yıl olmasından ötürü tarihsel incelemenin başlangıç noktası olarak uygun görülmüştür. Araştırmanın tarihsel kapsamının 1974 yılı ile sonlanmasının sebebi ise, adanın siyasal kaderini büyük oranda etkileyen iki gelişmenin, Yunan Cuntasının Kıbrıs’ta yaptırdığı darbe ile Türkiye’nin Kıbrıs Harekâtının o yıl yaşanmasıdır. Araştırma; Türkçe, Yunanca ve İngilizce tarihsel belgeler (arşivler, gazeteler ve hatıratlar) inceleyerek ilgili tarafların Kıbrıs siyasetlerine ışık tutmaya çalışmıştır. İncelenen dönemde Kıbrıslı Rum liderlerin anayasal değişiklikler vasıtasıyla adadaki Türk toplumunun veto haklarını sınırlandırmaya, Kıbrıslı Türk liderlerin ise ada Türkleri için yerel yönetimde özerklik hakkı elde etmeye çalıştıkları görüldü. İncelenen dönemde Yunanistan ile Kıbrıs Rum liderleri arasında ciddi çatışmalar ve görüş ayrılıkları yaşanırken Türkiye ile Kıbrıs Türk liderleri arasında uyum ve işbirliğinin egemen olduğu da çalışma tarafından ulaşılan dikkate değer bir sonuçtur.